Program Pelatihan Digital Marketing untuk Remaja Masjid: Menciptakan Enterpreneur Muda Islami di Desa Karyamekar Pasirwangi Garut : Pengabdian - Eti Jumiati; Puspita Chairun Nisa; Wati Rahayu; Ahmad Saepudin; Iman Sulaeman (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Digital Marketing Training Program for Mosque Youth in Karyamekar Village, Pasirwangi, Garut, was implemented as a form of community service aimed at improving digital literacy, entrepreneurial skills, and developing the character of ethical young Islamic entrepreneurs. This activity used a participatory approach through preparation, training, and ongoing mentoring. Participants, consisting of mosque youth aged 15–24, were trained in digital content creation, Islamic personal branding, and the use of business social media such as Instagram and WhatsApp Business. The results of the activity showed a significant increase in participants' knowledge and skills, marked by an average increase of 30% in post-test scores and the creation of independently managed digital business accounts. When compared with ten relevant studies in the past five years, this program excels in integrating Islamic values ​​and implementing a continuous mentoring system, which emphasizes the importance of religious ethics and the sustainability of digital training. Thus, this program not only contributes to improving participants' technical competence but also demonstrates that mosques can play a strategic role as centers for technology-based economic, social, and spiritual empowerment in rural areas.